Lignin-based polymer hydrogel as well as preparation method and application thereof

Through the preparation and application of lignin-based polymer hydrogel, the problems of poor water stability and insufficient water retention capacity in the sandy loess area in the Loess Plateau are solved, and soil improvement of biodegradable and efficient water-absorbing materials is achieved, and the moisture of the soil is enhanced Maintaining capacity avoids soil solidification and meets the needs of sustainable development.

CN119320479APending Publication Date: 2025-01-17CHANGAN UNIV +1

Patent Information

Application Number
CN202411439720.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The sandy loess area in the Loess Plateau area is loose soil, loose structure, poor water stability, and is easily washed by water flow, and there are serious problems of seepage and fertilizer seepage, resulting in drought and geological disasters. At the same time, existing soil improvement technology ignores the soil's water retention. Characteristics, difficult to support plant growth.

Method used

Using the preparation method of lignin-based polymer hydrogel, by mixing gelatin and sodium lignin sulfonate and adding polymerized monomer solution for polymerization, forming a biodegradable and efficient water-absorbing material, which is used to improve sand and soil and enhance its water-retaining properties. .

Benefits of technology

This method improves the biodegradability of lignin-based polymer hydrogels, reduces the potential impact on the environment, provides a gentle and effective soil water retention solution, significantly improves the soil's moisture retention capacity and avoids soil Stand-aligned, meets the needs of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320479A_ABST
    Figure CN119320479A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing a gelatin solution and sodium lignin sulfonate to obtain a mixed solution, heating the mixed solution to a set temperature, sequentially adding a polymeric monomer solution, potassium persulfate and N, N-dimethylformamide, and carrying out a reaction at a set temperature to obtain the lignin-based polymer hydrogel. Polymerizing with N, N-methylene bisacrylamide, and fully mixing to obtain the lignin-based polymer hydrogel after a gel state is formed; sodium lignin sulfonate and gelatin are adopted as bio-based raw materials, and compared with traditional lignin-based high-molecular hydrogel depending on petrochemical products, the lignin-based high-molecular hydrogel has the remarkable environment-friendly characteristic. The materials obtained from natural sources not only ensure the biodegradability of the lignin-based polymer hydrogel, but also can be naturally decomposed in soil application, so that the potential negative influence on an ecological system is greatly reduced. By using the lignin-based polymer hydrogel, secondary pollution in the environment is avoided, and the innovation potential of application of biological materials in environmental engineering and agricultural science and technology is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil improvement, and specifically relates to a lignin-based polymer hydrogel and a preparation method and application thereof. Background Art

[0002] In the Loess Plateau, due to the fragmented terrain and complex topography, loess soil can be divided into three main areas from northwest to southeast based on its particle size composition: sandy loess belt, loess belt and clay loess belt. The sandy loess area is easily eroded by water due to its loose soil, loose structure, poor water stability, and serious water and fertilizer infiltration problems, which often lead to drought. These characteristics further induce geological disasters and ecological problems, such as loess collapse, erosion disasters, embankment cracks, bridge deformation and serious soil and water loss. At the same time, due to its low water retention and storage capacity, it is difficult for plants to grow in such soils. Existing sandy soil improvement technologies, such as adding inorganic binders such as cement, fly ash and lime, are mainly aimed at improving the strength of sandy soil, but often ignore the water retention characteristics of the soil.

[0003] Lignin-based polymer hydrogel, a highly hydrophilic three-dimensional network polymer, can swell rapidly in water and retain a large amount of water in the swollen state without dissolving. It is widely used in the preparation of electrolytes, biosensors and various biomedical fields such as tissue engineering, regenerative medicine and drug delivery, but its application in soil improvement is relatively rare. At present, the materials used to prepare water-retaining lignin-based polymer hydrogels are mostly non-renewable petroleum-based monomers such as acrylic acid and acrylamide, which not only makes the preparation cost of lignin-based polymer hydrogels high, but also poses a threat to the soil and groundwater environment because it is difficult to degrade in the soil. Summary of the invention

[0004] The purpose of the present invention is to provide a lignin-based polymer hydrogel and a preparation method and application thereof to overcome the deficiencies of the prior art. The present invention can improve the biodegradability of acrylic acid-based lignin-based polymer hydrogels, thereby reducing their potential impact on the environment. The present invention can provide a new approach for the ecological restoration and sustainable management of sandy soil.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a lignin-based polymer hydrogel comprises the following steps: The following steps are involved: S1: Mix the gelatin solution and sodium lignin sulfonate, and stir to obtain a mixed solution.

[0006] S2: The mixed solution is heated to a set temperature, and the polymerization monomer solution, potassium persulfate and N,N-methylenebisacrylamide are added in sequence for polymerization and fully mixed to obtain a lignin-based polymer hydrogel after a gel is formed.

[0007] Preferably, the gelatin is heated to a set temperature in an aqueous solution, and stirring is continued during the heating process. After stirring at the set temperature for a set time, the temperature is then cooled to 45-50°C to obtain a gelatin solution for use. Inert gas is introduced into the gelatin during the stirring and dissolution of the aqueous solution.

[0008] Preferably, the usage ratio of gelatin to deionized water is (9-12) g:100 mL; the stirring temperature is set to 80-85° C., and the stirring time is 10-20 min.

[0009] Preferably, acrylic acid is neutralized with sodium hydroxide in an ice bath, and then the neutralized acrylic acid solution is mixed with 2-acrylamido-2-methylpropanesulfonic acid, and then ultrasonicated to obtain a polymerized monomer solution.

[0010] Preferably, the neutralization degree of acrylic acid is 75-85%; the mass ratio of acrylic acid to 2-acrylamido-2-methylpropanesulfonic acid is (7-8):(2-3).

[0011] Preferably, the mass ratio of sodium lignin sulfonate to the polymerized monomer solution in the lignin-based polymer hydrogel is (0.5-1):10; and the concentration of the gelatin solution is 9wt%-12wt%.

[0012] Preferably, the mass ratio of the mixed glue solution to the polymerized monomer solution is (1-2):10, and the mass of the polymerized monomer solution accounts for 25% of the mass of the total solution.

[0013] Preferably, the mass ratio of the polymerized monomer solution to potassium persulfate is 1:(0.13-0.15), and the mass ratio of the polymerized monomer solution to N,N-methylenebisacrylamide is 1:(0.014-0.016).

[0014] A lignin-based polymer hydrogel is prepared by adopting the preparation method.

[0015] An application of the above lignin-based polymer hydrogel, wherein the lignin-based polymer hydrogel is used as a water retaining agent for retaining soil moisture.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a lignin-based polymer hydrogel, wherein a gelatin solution and sodium lignin sulfonate are mixed, a mixed solution is obtained after stirring, the mixed solution is heated to a set temperature, a polymerization monomer solution is added in sequence, potassium persulfate and N,N-methylenebisacrylamide are polymerized and fully mixed, and a lignin-based polymer hydrogel is obtained after a gel is formed; the invention adopts sodium lignin sulfonate and gelatin as bio-based raw materials, and has significant environmentally friendly characteristics compared with traditional lignin-based polymer hydrogels that rely on petrochemical products. These materials obtained from natural sources not only ensure the biodegradability of lignin-based polymer hydrogels, but also can be naturally decomposed in soil applications, greatly reducing the potential negative impact on the ecosystem. Therefore, the use of the lignin-based polymer hydrogel avoids secondary pollution in the environment, meets the needs of sustainable development, and demonstrates the innovative potential of applying biomaterials in environmental engineering and agricultural science and technology.

[0017] Preferably, a highly efficient water-absorbing material is formed by combining sodium lignin sulfonate, gelatin, acrylic acid and 2-acrylamido-2-methylpropane sulfonic acid.

[0018] The lignin-based polymer hydrogel prepared by the above method, the sodium lignin sulfonate contained therein and other ingredients work together to greatly enhance its water absorption performance. Experimental data show that the maximum water absorption rate of the lignin-based polymer hydrogel can reach 1921g / g, demonstrating its potential application value in multiple fields. In addition, the present invention also explores the application of the double lignin-based polymer hydrogel in soil improvement. Compared with traditional soil conditioners, these traditional materials mostly reduce water penetration through soil solidification. Although they can increase the water retention of the soil, they often cause soil compaction and have an adverse effect on the physical and chemical properties and structure of the soil. On the contrary, the lignin-based polymer hydrogel in the present invention can be simply mixed with the soil without having a negative impact on the physical and chemical properties and structure of the soil. The lignin-based polymer hydrogel relies on its inherent water absorption properties to maintain moisture in the soil, thereby providing a more gentle and effective soil water retention solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the preparation process of lignin-based polymer hydrogel in an embodiment of the present invention.

[0020] Figure 2 This is a picture of the lignin-based polymer gel prepared in an embodiment of the present invention after crushing and sieving, as well as a picture of water absorption and swelling.

[0021] Figures 3a to 3iLS / G / P (AA-co-AMPS) hydrogels of different mesh sizes (10<m<40, 40<m<80, 80<m<100) were placed in soils of different mesh sizes (10<m<40 (coarse sand), 40<m<60 (medium sand), 60<m<100 (fine sand)) to obtain their saturated hydraulic conductivity.

[0022] Figure 4a A schematic diagram of the water retention rate of the LS / G / P (AA-co-AMPS) hydrogel of the present invention in soil obtained by mixing it with coarse sand; Figure 4b It is a schematic diagram of the water retention rate of the LS / G / P (AA-co-AMPS) hydrogel of the present invention in soil obtained by mixing it with medium sand; Figure 4c This is a schematic diagram of the water retention rate of the LS / G / P (AA-co-AMPS) hydrogel of the present invention in soil obtained by mixing it with fine sand.

[0023] Figure 5a , Figure 5b , Figure 5c They respectively represent the daily evaporation obtained when the LS / G / P (AA-co-AMPS) hydrogel of the present invention is applied to soils with mesh sizes of 10<m<40 (coarse sand), 40<m<60 (medium sand), and 60<m<100 (fine sand). DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0026] The present invention provides a method for preparing a lignin-based polymer hydrogel, which improves the biodegradability of an acrylic acid-based lignin-based polymer hydrogel and thereby reduces its potential impact on the environment. The method specifically comprises the following steps: S1: Mix the gelatin solution and sodium lignin sulfonate, and stir to obtain a mixed solution.

[0027] S2: The mixed solution is heated to a set temperature, and the polymerization monomer solution, potassium persulfate and N,N-methylenebisacrylamide are added in sequence for polymerization and fully mixed to obtain a lignin-based polymer hydrogel after a gel is formed.

[0028] Specifically, the gelatin solution is prepared by dissolving gelatin in an aqueous solution under an inert gas atmosphere.

[0029] The preparation method of the gelatin solution specifically includes the following steps: heating the gelatin in an aqueous solution to a set temperature, continuously stirring during the heating process, maintaining the set temperature and stirring for a set time, then cooling the temperature to 45-50°C to obtain a gelatin solution for use, and introducing nitrogen into the gelatin during the stirring and dissolution of the aqueous solution.

[0030] The usage ratio of gelatin and deionized water is (9-12) g:100 mL; the stirring temperature is set to 80-85° C., and the stirring time is 10-20 min.

[0031] The specific preparation process of the polymerization monomer solution is as follows: neutralizing acrylic acid with sodium hydroxide in an ice bath, then mixing the neutralized acrylic acid solution with 2-acrylamide-2-methylpropanesulfonic acid, and obtaining the polymerization monomer solution after ultrasonic treatment.

[0032] The acrylic acid neutralization degree is 75-85%.

[0033] The mass ratio of acrylic acid to 2-acrylamido-2-methylpropanesulfonic acid is (7-8): (2-3).

[0034] In S1, the mass ratio of sodium lignin sulfonate and polymerized monomer solution in the lignin-based polymer hydrogel is (0.5-1):10; the stirring is performed at 80-85°C for 10-20 min.

[0035] In S1, the gelatin solution is obtained by mixing gelatin and deionized water; the concentration of the gelatin solution is 9wt%~12wt%.

[0036] The molecular weight of the gelatin is 50,000 to 100,000.

[0037] In S2, the mass ratio of the mixed glue solution to the polymerization monomer solution is (1~2):10.

[0038] In S2, the mass of the polymerization monomer solution accounts for 25% of the total solution mass.

[0039] In S2, the mass ratio of the polymerized monomer solution to potassium persulfate is 1: (0.13~0.15) In S2, the mass ratio of the polymerized monomer solution to N,N-methylenebisacrylamide is 1:(0.014~0.016).

[0040] The lignin-based polymer hydrogel obtained after being fully mixed and formed into a gel state was repeatedly washed with 80% ethanol and deionized water, and then freeze-dried, crushed, and sieved to obtain sodium lignin sulfonate / gelatin / polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid lignin-based polymer hydrogels of different mesh sizes.

[0041] In a specific embodiment of the present application, a lignin-based polymer hydrogel and a preparation method thereof are provided, wherein gelatin is dissolved in deionized water, stirred at 80°C for 10 minutes, and the solution is cooled to room temperature to obtain a gelatin solution; The acrylic acid is placed in an ice bath, and sodium hydroxide is added to obtain neutralized acrylic acid; then 2-acrylamide-2-methylpropanesulfonic acid solution is added, and the mixture is placed in an ultrasonic cleaning machine for 30 minutes to obtain a polymerized monomer solution; Sodium lignin sulfonate is dissolved in deionized water according to a certain proportion, mixed with gelatin solution, heated and stirred to make the sodium lignin sulfonate and gelatin solution evenly mixed, and then the polymerization monomer solution is added and stirred; the above solutions are fully mixed, and then potassium persulfate and N,N-methylenebisacrylamide are added dropwise using a rubber-tipped dropper, and left to stand for 2 hours to obtain a lignin-based polymer hydrogel; The gel was repeatedly washed with 80% ethanol and deionized water, and then freeze-dried, crushed, and sieved to obtain sodium lignin sulfonate / gelatin / polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid lignin-based polymer hydrogels of different mesh sizes.

[0042] An application of the lignin-based polymer hydrogel prepared by the above method in soil is that after lignin-based polymer hydrogel water retaining agents of different mesh sizes are uniformly mixed with sand in a certain proportion, they are loaded into a ring knife and soaked in water for 24 hours to allow the lignin-based polymer hydrogel water retaining agent to be fully saturated with water. Then, the ring knife method is used to measure the saturated hydraulic conductivity of the soil to reflect the water retention capacity of the water retaining agent in the soil.

[0043] The bulk density of the sand used is 1.50g / cm3 and the moisture content is 4.9%.

[0044] The mixing ratios of lignin-based polymer hydrogel water-retaining agent and sandy soil were 0, 0.05%, 0.1%, and 0.15%.

[0045] Explanation of terms involved in this invention: LS: sodium lignin sulfonate; G: gelatin; AA: acrylic acid; AMPS: 2-acrylamido-2-methylpropanesulfonic acid solution; KPS: potassium persulfate; MBA: N,N-methylenebisacrylamide; NaOH: sodium hydroxide; LS / G / P (AA-co-AMPS): sodium lignin sulfonate / gelatin / polyacrylic acid-2-acrylamido-2-methylpropanesulfonic acid lignin-based polymer hydrogel.

[0046] Example 1 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0047] S2: Take 10 ml and mix it with sodium lignin sulfonate solution, stir at 50°C for 30 minutes, add polymerization monomer + solution after the solution is fully mixed, add 0.14g potassium persulfate and 0.015g N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 85°C and continue stirring, stop stirring after gel is formed, and keep for 2-3 hours.

[0048] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0049] Example 2 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0050] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.14 potassium persulfate and 0.013N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 85°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0051] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0052] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 1. The results showed that the swelling ratio of the polymer hydrogel was 1789 times, and 97 times in physiological saline. Example 3 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 12g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0053] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add potassium persulfate and N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0054] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0055] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 2. The results showed that the swelling ratio of the polymer hydrogel was 1549 times, and 68 times in physiological saline. Example 4 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 0.5g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0056] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.12 g of potassium persulfate and 0.015 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0057] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0058] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 3. The results showed that the swelling ratio of the polymer hydrogel was 1349 times, and 49 times in physiological saline. Example 5 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 0.5g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 7g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 3g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0059] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.14 g of potassium persulfate and 0.015 N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0060] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0061] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 4. The results showed that the swelling ratio of the polymer hydrogel was 1349 times, and 49 times in physiological saline. Example 6 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 7g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 85%, and then mix it with 3g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0062] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.13 g of potassium persulfate and 0.014 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 85°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0063] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0064] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 5. The results showed that the swelling ratio of the polymer hydrogel was 1249 times, and 58 times in physiological saline. Example 7 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 85%, and then mix it with 2g of 2-acrylamido-2-methylpropanesulfonic acid. After ultrasonicating the mixed solution for 30min, get the polymerization monomer solution.

[0065] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.13 g of potassium persulfate and 0.014 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 85°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0066] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0067] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 6. The results showed that the swelling ratio of the polymer hydrogel was 1449 times, and 75 times in physiological saline. Example 8 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 11g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 75%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. After ultrasonicating the mixed solution for 30min, get the polymerization monomer solution.

[0068] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.12 g of potassium persulfate and 0.015 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 85°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0069] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0070] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 7. The results showed that the swelling ratio of the polymer hydrogel was 1598 times, and 78 times in physiological saline. Example 9 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 12g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0071] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.13 g of potassium persulfate and 0.012 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0072] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0073] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 8. The results showed that the swelling ratio of the polymer hydrogel was 1625 times, and 81 times in physiological saline. Example 10 A method for preparing a lignin-based polymer hydrogel comprises the following steps: S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0074] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.12 g of potassium persulfate and 0.012 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep stirring for 2-3 hours.

[0075] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0076] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 9. The results showed that the swelling ratio of the polymer hydrogel was 1821 times, and 98 times in physiological saline.

[0077] Embodiment 11 A method for preparing lignin-based polymer lignin-based polymer hydrogel S1: Dissolve 10g of gelatin solution in 100ml of deionized water, heat to 80°C, stir for 10min until the solution is homogeneous, and cool to room temperature for use. Get gelatin solution. Dissolve 1g of sodium lignin sulfonate in 5ml of water, and ultrasonicate for 30min to get sodium lignin sulfonate solution. Get 8g of acrylic acid, neutralize it with 20% sodium hydroxide in an ice bath, the neutralization degree is 80%, and then mix it with 2g of 2-acrylamido-2-methylpropane sulfonic acid. Ultrasonicate the mixed solution for 30min to get a polymerization monomer solution.

[0078] S2: Take 10 ml of gelatin solution and mix it with sodium lignin sulfonate solution, stir it at 50°C for 30 minutes, add the polymerization monomer solution after the solution is fully mixed, add 0.14 g of potassium persulfate and 0.012 g of N,N-methylenebisacrylamide in sequence, stir for 10 minutes, heat to 80°C and continue stirring, stop stirring after gel is formed, and keep it for 2-3 hours.

[0079] S3: Take out the sample and remove the unreacted monomer and sodium lignin sulfonate with 80% ethanol and deionized water. Finally, freeze-dry, crush and sieve to obtain lignin-based polymer gel.

[0080] The water absorption performance of the obtained polymer hydrogel was tested according to the method of Example 10. The results showed that the swelling ratio of the polymer hydrogel was 1921 times, and 98 times in physiological saline. Application Example 1 According to the soil bulk density of 1.5g / cm 3 LS / G / P (AA-co-AMPS) hydrogel prepared in Example 1 with different mesh sizes (10 < m < 40, 40 < m < 60, 60 < m < 100) was weighed and mixed with 150.0 g (0), 150.0 g (0.05%), 149.85 g (0.1%), and 149.78 g (0.15%) of sand. Finally, the mixed sand was placed in a 100 cm 3 The ring cutter was placed in water and soaked for 24 hours, then fixed on the measuring device to measure the saturated hydraulic conductivity. The sand was sieved to separate the coarse sand (10<m<40), (medium sand 40<m<60), and fine sand (60<m<100) and the hydraulic conductivity was measured respectively.

[0081] Application Example 2 According to the soil bulk density, the LS / G / P (AA-co-AMPS) hydrogel prepared in Example 1 with a mesh size of (40 < m < 80) was weighed and placed in soils with different mesh sizes (10 < m < 40 (coarse sand), 40 < m < 60 (medium sand), 60 < m < 100 (fine sand)). The soil mass was 100 ± 0.5 g and evenly mixed in a beaker with a volume of 250 ml. 50 ml of deionized water was added and placed in a constant temperature and humidity incubator. The temperature was set to 35° C. and the relative humidity was 40%. The mass change of the beaker was recorded every day, and the water retention rate was calculated.

[0082] Application Example 3 According to the soil bulk density, 40-80 mesh of LS / G / P (AA-co-AMPS) hydrogel prepared in Example 1 was weighed and mixed with soil with m>2 mm, and then placed in a ring cutter with filter paper on the bottom. After soaking for 12 hours, the ring cutter was removed and allowed to stand. After excluding gravity water, the ring cutter was placed in the room, and the mass of the ring cutter was weighed at a specified time every day to calculate the daily evaporation.

[0083] Figure 2 This is a graph of the lignin-based polymer gel after crushing and sieving and a graph of water absorption and swelling. Figure 2 It can be seen that after the powdered gel particles are soaked in water for a period of time, the hydrogel absorbs water and becomes saturated and amorphous.

[0084] Figure 3 shows the saturated hydraulic conductivity of LS / G / P (AA-co-AMPS) (10<m<40, 40<m<80, 80<m<100) hydrogels of different mesh sizes (10<m<40 (coarse sand), 40<m<60 (medium sand), 60<m<100 (fine sand)) placed in soils of different mesh sizes. Figures abc show the saturated hydraulic conductivity of the soil when the hydrogel particle size is 40<m<80; 10<m<40; SAP m>80 respectively: Figure def shows the saturated hydraulic conductivity of the soil when the hydrogel particle size is 40<m<80; 10<m<40; SAP m>80 respectively; Figure ghi shows the saturated hydraulic conductivity of the soil when the hydrogel particle size is 40<m<80; 10<m<40; SAP m>80 respectively.

[0085] Depend on Figure 3a , Figure 3b , Figure 3c , the hydraulic conductivity reduction trend in coarse sand is similar to that of fine and medium sand, but the overall hydraulic conductivity is higher, which indicates that the coarse sand has greater porosity and permeability. Figure 3d , Figure 3e , Figure 3fThe hydraulic conductivity decreased significantly with the increase of hydrogel addition. The 0.15% hydrogel addition showed the largest decrease in hydraulic conductivity, indicating that a higher proportion of hydrogel can more effectively reduce water circulation in fine-grained soils. Figure 3g , Figure 3h , Figure 3i It can be seen that in medium sand, the same trend of decreasing water conductivity with increasing amount of hydrogel added was observed. Since the particle size of medium sand is between fine sand and coarse sand, the reduction of water conductivity is also moderate, and 0.15% hydrogel still shows the best effect. A higher hydrogel ratio (0.15%) shows better water reduction effect in all soil types because more hydrogel can absorb and retain more water.

[0086] FIG4 shows the water retention rate of the LS / G / P (AA-co-AMPS) hydrogel of the present invention mixed with soils of different mesh sizes. Figure 4a , Figure 4b , Figure 4c They represent soil mesh size of 10<m<40 (coarse sand), 40<m<60 (medium sand), 60<m<100 (fine sand), and the hydrogel addition amount is 0.05%, 0.1%, and 0.15%, respectively. The experimental results show that in the three sands with different particle sizes, the addition of 0.15% hydrogel generally shows the best water retention effect, and the water retention rate increases with the increase of the addition amount. The water retention rate of fine sand in the later stage of the experiment is higher than that of coarse sand and medium sand, indicating that the water retention effect of hydrogel is more lasting in finer soil particle sizes.

[0087] Figure 5a , Figure 5b , Figure 5c They respectively represent the daily evaporation obtained when the LS / G / P (AA-co-AMPS) hydrogel of the present invention is applied to soils with mesh sizes of 10<m<40 (coarse sand), 40<m<60 (medium sand), and 60<m<100 (fine sand), Figure 5a , Figure 5b , Figure 5c It is shown that in all soil types, 0.15% hydrogel addition showed the best evaporation control effect. This shows that increasing the proportion of hydrogel helps to better control water evaporation. In application scenarios where water evaporation needs to be controlled, using a higher proportion of hydrogel (such as 0.15%) will provide better results, especially in fine-grained soils.

[0088] The invention discloses a method for preparing a lignin-based polymer hydrogel. In the process of preparing a highly absorbent resin, sodium lignin sulfonate, gelatin, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid are combined to form an efficient water-absorbing material; sodium lignin sulfonate and gelatin are mixed and stirred, and neutralized acrylic acid and 2-acrylamide mixed solution, potassium persulfate, and N,N-methylenebisacrylamide are sequentially added at a specified temperature; after the gel is formed, unreacted monomers are washed away with ethanol and water, and finally freeze-dried to obtain a lignin-based polymer hydrogel material. The present invention uses sodium lignin sulfonate and gelatin as bio-based raw materials, which have significant environmentally friendly characteristics compared to traditional lignin-based polymer hydrogels that rely on petrochemical products; these materials obtained from natural sources not only ensure the biodegradability of lignin-based polymer hydrogels, but also can be naturally decomposed in soil applications, greatly reducing the potential negative impact on the ecosystem. Therefore, the use of the lignin-based polymer hydrogel avoids secondary pollution in the environment, meets the needs of sustainable development, and demonstrates the innovative potential of applying biomaterials in environmental engineering and agricultural technology.

[0089] The present invention further details the lignin-based polymer hydrogel prepared by the aforementioned method, wherein the sodium lignin sulfonate contained therein acts together with other ingredients to greatly enhance its water absorption performance. Experimental data show that the maximum water absorption rate of the lignin-based polymer hydrogel can reach 1921g / g, demonstrating its potential application value in multiple fields. In addition, the present invention also explores the application of the dual lignin-based polymer hydrogel in soil improvement. Compared with traditional soil conditioners, these traditional materials mostly reduce water penetration through soil solidification. Although they can increase the water retention of the soil, they often cause soil compaction, which has an adverse effect on the physical and chemical properties and structure of the soil. On the contrary, the lignin-based polymer hydrogel in the present invention can be simply mixed with the soil without having a negative impact on the physical and chemical properties and structure of the soil. The lignin-based polymer hydrogel relies on its inherent water absorption properties to maintain moisture in the soil, thereby providing a more gentle and effective soil water retention solution.

Claims

1. A method for preparing a lignin-based polymer hydrogel, characterized in that: The following steps are involved: The following steps are involved: S1: mixing the gelatin solution and sodium lignin sulfonate, and stirring to obtain a mixed solution; S2: The mixed solution is heated to a set temperature, and the polymerization monomer solution, potassium persulfate and N,N-methylenebisacrylamide are added in sequence for polymerization and fully mixed to obtain a lignin-based polymer hydrogel after a gel is formed.

2. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: The gelatin is heated to a set temperature in an aqueous solution, and stirring is continued during the heating process. After stirring at the set temperature for a set time, the temperature is then lowered to 45-50°C to obtain a gelatin solution for use. Inert gas is introduced into the gelatin during the stirring and dissolution of the aqueous solution.

3. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: The usage ratio of gelatin and deionized water is (9-12) g:100 mL; the stirring temperature is set to 80-85° C., and the stirring time is 10-20 min.

4. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: Acrylic acid is neutralized with sodium hydroxide in an ice bath, and then the neutralized acrylic acid solution is mixed with 2-acrylamido-2-methylpropanesulfonic acid, and a polymerization monomer solution is obtained after ultrasonic treatment.

5. The method for preparing a lignin-based polymer hydrogel according to claim 4, characterized in that: The neutralization degree of the acrylic acid is 75-85%; the mass ratio of the acrylic acid to 2-acrylamido-2-methylpropanesulfonic acid is (7-8): (2-3).

6. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: The mass ratio of sodium lignin sulfonate and polymerized monomer solution in the lignin-based polymer hydrogel is (0.5-1):10; the concentration of the gelatin solution is 9wt%-12wt%.

7. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: The mass ratio of the mixed glue solution to the polymerized monomer solution is (1-2):10, and the mass of the polymerized monomer solution accounts for 25% of the mass of the total solution.

8. The method for preparing a lignin-based polymer hydrogel according to claim 1, characterized in that: The mass ratio of the polymerized monomer solution to potassium persulfate is 1:(0.13-0.15), and the mass ratio of the polymerized monomer solution to N,N-methylenebisacrylamide is 1:(0.014-0.016).

9. A lignin-based polymer hydrogel, characterized in that: The method is prepared by any one of claims 1 to 9.

10. The use of the lignin-based polymer hydrogel according to claim 9, characterized in that: The lignin-based polymer hydrogel serves as a water retaining agent for retaining soil moisture.

Citation Information

Patent Citations

  • Preparation method of water-absorbing gel containing animal and plant fibers and inorganic nanoparticles

    CN102643498A

  • Preparation method of bio-based fully-degradable super absorbent gel

    CN118638324A

Cited By

  • Soil conditioner

    CN122060504A